2002
DOI: 10.1300/j070v12n01_06
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Incarcerated, Sexually-Abused Adolescent Females: An Outcome Study

Abstract: This study examined the psychosocial functioning of 100 adolescent females (ages 12-17) sentenced to secure care in a southeastern state and the impact of gender-specific, cognitive-behavioral therapy (CBT) intervention on the psychosocial functioning of subjects who reported a history of sexual abuse. The Multidimensional Adolescent Assessment Scale (MAAS) was used to assess psychosocial functioning. Pre-test scores on the MAAS revealed significantly higher scores on 12 of 16 dimensions of psychosocial functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 26 publications
0
20
0
1
Order By: Relevance
“…12, No. 1, January 2006 battering relationships (Arnold et al, 2003;Chesney-Lind, 1997;McCabe et al, 2002). Female participants in this sample were more than 15 times more likely to report unwanted sexual contact than males.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…12, No. 1, January 2006 battering relationships (Arnold et al, 2003;Chesney-Lind, 1997;McCabe et al, 2002). Female participants in this sample were more than 15 times more likely to report unwanted sexual contact than males.…”
Section: Discussionmentioning
confidence: 84%
“…Some researchers have argued that abuse, in particular sexual abuse, plays a larger role in the pathway to delinquency for female than for male adolescents (Hoyt & Scherer, 1998). Consistent with this belief, several studies have found higher rates of sexual abuse among incarcerated girls compared with boys (Anaya, Cantwell, & RotheramBorus, 2003;Arnold et al, 2003).…”
mentioning
confidence: 96%
“…Identified programs such as Go for Greatness (Guthrie & Flinchbaugh, 2001), Girl Talk (Schafer & Rosay, 2003;Schaffner, 2006), GirlRising (Beck, Bermudez, & King, 2003), and the Girls' Advocacy Project (Lederman & Brown, 2000) did not have evidence of evaluated effects. On occasion, outcome evaluations were available but lacked a description of the program itself (E. M. Arnold et al, 2003) or of the evaluation design (Daniel, 1999). Clearly, there is a focus on program content and development in this literature, with availability of program outcomes lacking behind.…”
Section: Resultsmentioning
confidence: 99%
“…While some authors have been interested in street-involved young women as an "at risk" population that needs to be protected, others have denounced a vast corpus of studies focusing on their delinquency (Bellot, Sylvestre, & St-Jacques, 2013;Campbell & Eid, 2009). Both homelessness and criminal behaviors are associated with violence and family conflict experienced by young women during childhood (Arnold et al, 2002;Belknap & Holsinger, 1998;Dhillon, 2011;Loper, 1999;McCabe, Lansing, Garland, & Hough, 2002;Medrano et al, 1999). While family factors and interpersonal violence experienced in the street are well known, there is a lot to understand about how institutions could reinforce violence and homelessness among street-involved young women.…”
Section: Introductionmentioning
confidence: 99%